Investigation of serum Cu, Zn, Fe and Se concentrations during pregnancy (60, 100 and 150 days) and after parturition (45 days) in single and twin pregnant sheep - Gurdogan, Fuat; Yildiz, Atilla; Balikci, Engin (Tubitak Scientific & Technological Research Council Turkey, 2006)
This study was conducted to determine the serum Cu, Zn, Se and Fe concentrations at 60, 100, and 150 days of pregnancy and at 45 days of parturition in twin and single pregnant sheep. A total of 30 pregnant Akkaraman sheep in 2 groups (15 single pregnancies, 15 twin pregnancies), aged 3-5 years and weighing 40-50 kg were used. The blood samples were analyzed for serum Cu, Zn, Se and Fe concentrations. No statistically significant difference was found for Se, Cu, Fe and Zn concentrations between the twin and single pregnancy groups. Insignificant decreases (P > 0.05) in serum Zn and Cu concentrations and significant decreases in serum Fe and Se concentrations were determined in the twin (P < 0.01, P < 0.01) and single (P < 0.05, P < 0.01) groups respectively at 60, 100 and 150 days of pregnancy. Except for Cu, the element concentrations increased steadily at 45 days of parturition compared to the pregnancy periods in both groups.
Keywords: pregnancy; copper; zinc; selenium; iron; sheep; after parturition